Health service readiness to provide care for HIV and cardiovascular disease risk factors in low- and middle-income countries. - Neil Cockburn; David Flood; Jacqueline A Seiglie; Jennifer Manne-Goehler; Krishna Aryal; Khem Karki; Albertino Damasceno; Rifat Atun; Sebastian Vollmer; Till Bärnighausen; Pascal Geldsetzer; Mary Mayige; et al. (Public Library of Science (PLoS), 2023)
Cardiovascular disease risk factors (CVDRF), in particular diabetes and hypertension, are chronic conditions which carry a substantial disease burden in Low- and Middle-Income Countries. Unlike HIV, they were neglected in the Millenium Development Goals along with the health services required to manage them. To inform the level of health service readiness that could be achieved with increased attention, we compared readiness for CVDRF with that for HIV. Using data from national Service Provision Assessments, we describe facility-reported readiness to provide services for CVDRF and HIV, and derive a facility readiness score of observed essential components to manage them. We compared HIV vs CVDRF coverage scores by country, rural or urban location, and facility type, and by whether or not facilities reported readiness to provide care. We assessed the factors associated with coverage scores for CVDRF and HIV in a multivariable analysis. In our results, we include 7522 facilities in 8 countries; 86% of all facilities reported readiness to provide services for CVDRF, ranging from 77-98% in individual countries. For HIV, 30% reported of facilities readiness to provide services, ranging from 3-63%. Median derived facility readiness score for CVDRF was 0.28 (IQR 0.16-0.50), and for HIV was 0.43 (0.32-0.60). Among facilities which reported readiness, this rose to 0.34 (IQR 0.18-0.52) for CVD and 0.68 (0.56-0.76) for HIV. Derived readiness scores were generally significantly lower for CVDRF than for HIV, except in private facilities. In multivariable analysis, odds of a higher readiness score in both CVDRF or HIV care were higher in urban vs rural and secondary vs primary care; facilities with higher CVDRF scores were significantly associated with higher HIV scores. Derived readiness scores for HIV are higher than for CVDRF, and coverage for CVDRF is significantly higher in facilities with higher HIV readiness scores. This suggests possible benefits from leveraging HIV services to provide care for CVDRF, but poor coverage in rural and primary care facilities threatens Sustainable Development Goal 3.8 to provide high quality universal healthcare for all.